Stenotrophomonas maltophilia pneumonia in a premature infant - Özkan, Hasan; Paşaoğlu, Güven; Olgaç, Nihal; Günel, Ruhi; Yüce, Ayşe; Gülay, Zeynep (The Turkish Journal of Pediatrics, 1999)
Stenotrophomonas (Xanthomonas) maltophilia is an aerobic, non-fermentative, Gram-negative bacillus that is generally considered an opportunistic pathogen. Infections due to S. maltophilia have become increasingly important in the hospital environment. Patients compromised by debilitating illnesses, surgical procedures or indwelling vascular catheters are most prone to S. maltophilia infections. To our knowledge, we report the first case of S. maltophilia pneumonia in a premature infant of 31 weeks gestational age. Although the therapy of choice for severe infections caused by S. maltophilia remains to be decided, this patient was successfully treated by amikacin.